In vivo Targeted Delivery of Extracellular Vesicle‒Gold Nanorod Hybrids to Metastatic Melanoma Lung Tumors - Bolaños K; León D; Jara-Guajardo P; Contreras P; Silva Ancahuail D; Riveros AL; Montano Y; Pérez D; Araya E; Kogan MJ; Quest AFG (International Journal of Nanomedicine)
Karen Bolaños,1– 3 Daniela León,1– 3 Pedro Jara-Guajardo,2,3 Pamela Contreras,1 David Silva Ancahuail,3 Ana Luisa Riveros,2,3 Yanay Montano,2,3 Damián Pérez,2,3 Eyleen Araya,4 Marcelo J Kogan,2,3 Andrew FG Quest1,3 1Laboratory of Cellular Communication, Center for Studies on Exercise, Metabolism and Cancer (CEMC), Program of Cell and Molecular Biology, Faculty of Medicine, Institute of Biomedical Sciences (ICBM), University of Chile, Santiago, Chile; 2Departamento de Quimica Farmacologica y Toxicologica, Facultad de Ciencias Quimicas y Farmaceuticas, Universidad de Chile, Santiago, Chile; 3Advanced Center for Chronic Diseases (ACCDIS), Facultad de Medicina and Facultad de Ciencias Quimicas y Farmaceuticas, Santiago, Chile; 4Departamento de Ciencias Quimicas, Facultad de Ciencias Exactas, Universidad Andres Bello, Santiago, ChileCorrespondence: Marcelo J Kogan, Departamento de Química Farmacológica y Toxicológica, Facultad de Ciencias Químicas y Farmacéuticas, Universidad de Chile, Santiago, 8380494, Chile, Email mkogan@ciq.uchile.cl Andrew FG Quest, Cellular Communication Laboratory, Center for Studies on Exercise, Metabolism and Cancer (CEMC), Instituto de Ciencias Biomédicas (ICBM), Facultad de Medicina, Universidad de Chile, Santiago, 8380453, Chile, Email aquest@u.uchile.clBackground: Cutaneous melanoma is an aggressive type of cancer characterized by rapid progression, resistance to chemotherapy, and metastasis to the lung. Conventional chemotherapy and radiotherapy are the principal approaches for treating metastasizing tumors, but the lack of targeting results in severe side effects and low treatment efficacy. Nanoparticles reportedly increase selectivity, given that they can accumulate at specific locations owing to the enhanced permeation and retention (EPR) effect. In this respect, plasmonic nanoparticles, such as gold nanorods (AuNRs), are interesting because of their photothermal and optical properties, making them suitable for biomedical applications, such as drug delivery, tumor ablation, and theranostics. To increase the tumor accumulation of AuNRs, extracellular vesicles (with sizes ranging from 40– 150 nm) have attracted attention because of their remarkable biocompatibility and natural cell-accumulation selectivity. To further increase the targeting properties of the nanosystem, we functionalized the AuNRs with methotrexate (MTX), which is known to interact with the overexpressed folate receptors in cancer cells. We combined the inherent homing properties of exosomes from B16F10 cells with the active targeting properties of MTX to increase the accumulation of AuNRs in metastatic lung melanoma tumors.Methods: We obtained and exhaustively characterized B16F10 exosomes loaded with MTX-functionalized AuNRs (EXOS-AuNR-MTX). The safety of the complete nanosystem, as well as its specific and time-dependent accumulation in B16F10 cells, was determined using the mitochondrial MTS assay and fluorescence analysis, respectively.Results: Surface functionalization with MTX in combination with B16F10 EXOS was used to promote the accumulation of AuNRs in metastatic lung nodules, with significantly greater amounts of gold in the tumors following EXOS-AuNR-MTX treatment than following only AuNR-MTX treatment, as was determined in vivo and ex vivo by quantitative gold measurements. Remarkably, 5.5% of the injected dose of the AuNRs was recovered at the tumor sites, whereas only 1% of the injected dose usually accumulated in tumors due to the EPR effect, as reported. We further confirmed the preferential accumulation of AuNRs from EXOS-AuNR-MTX rather than from AuNR-MTX in tumor vessels and tumor nodules rather than healthy tissues by histological analysis.Conclusion: Our approach provides a valuable tool to improve the accumulation of gold nanoparticles in metastatic tumor nodules by combining the natural properties of exosomes to drive the targeting of AuNR-MTX. Keywords: exosomes, gold nanorods, methotrexate, targeting, drug delivery, metastasis